2021
DOI: 10.52547/jfl.9.37.125
|View full text |Cite
|
Sign up to set email alerts
|

Online Teacher Quality and TPACK Framework of Knowledge: EFL Pre-service Teachers' Views

Abstract: This study aimed at examining prospective EFL teachers' views about quality of online English language teaching and Technological Pedagogical Content Knowledge (TPACK) and the related skills. To this end, the viewpoints of 100 graduate students of TEFL (M = 23, F = 77

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…On the other hand, the analysis also indicates that technological knowledge obtained the lowest mean rating of 3.80. This corroborates with the findings of Basirat & Taghizadeh (2021) which revealed that teachers generally perceived their technological knowledge to be the lowest TPACK component.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, the analysis also indicates that technological knowledge obtained the lowest mean rating of 3.80. This corroborates with the findings of Basirat & Taghizadeh (2021) which revealed that teachers generally perceived their technological knowledge to be the lowest TPACK component.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, novice teachers were given significantly higher scores considering their technological knowledge, technological content knowledge, and technological pedagogical knowledge. In conjunction with these findings, a study conducted by Basirat and Taghizadeh (2021) revealed that among the seven categories of the TPACK framework, students considered content knowledge and pedagogical knowledge the first and second most significant frames of knowledge for an online teacher, respectively whereas technological knowledge and technological content knowledge received the lowest one. In addition, other studies also pointed out that the knowledge dimensions of TPACK, including technology, are dependent on age and teaching experience.…”
Section:  Introductionmentioning
confidence: 84%
“…Sixth, avoid irrelevant material. Basirat & Taghizadeh (2021) argue that while basic teacher training aims to build competency, training should focus on a minimum set of specific competencies for diverse tasks and roles. This is done by designing messages, of course, needing to pay attention that what is conveyed is only important information, providing temporal boundaries, keys to be studied, and discussion topics.…”
Section: Discussionmentioning
confidence: 99%
“…However, using proper TPCK, teachers can motivate learners to investigate English learning material, and the model indicates that CK, which combines technology and educational capabilities, is vital for facilitating efficient and innovative classroom education (Mishra & Koehler, 2006). Moreover, Shadiev and Yang (2020) recommended incorporating technology into the teaching and learning process, where teachers could regulate their educational tasks, as well as their educational tactics, to effectively employ the present sources in the best way possible (Basirat and Taghizadeh, 2021;Tondeur et al, 2012). Simultaneously, using technology for teaching, practicing, assessing, and learning a foreign language has several advantages, particularly in EFL contexts where students have few opportunities to practice and evaluate their language abilities (Alsied & Pathan, 2013).…”
Section: Efl Teachers' Lacks On the Scopes Of Efl Teachers' Cpdmentioning
confidence: 99%